From Manual to Digital: How Assalafie Babakan Mobile is Revolutionizing Administrative Systems in Islamic Boarding Schools? - Ripai, Ahmad; Santoso, Sigit; Asilah, Asilah (JURNAL AL-TANZIM, 2025)
This study aims to analyze the implementation of the Assalafie Babakan Mobile application in managing administration in an Islamic boarding school. This application is designed to improve efficiency and transparency and facilitate communication between Islamic boarding school administrators, guardians of students, and students. In this study, a qualitative approach was used to understand the application's process. Data were collected through interviews, observations, and documentation. The data analysis process was carried out in several stages: data reduction, data presentation, analysis of findings, and conclusion. The study results showed that the implementation of this application succeeded in improving the management of Islamic boarding school administration, facilitating communication, and monitoring student development. This application also provides convenience in managing student data more efficiently and in an organized manner. This application positively contributes to the digitalization process in Islamic boarding schools, especially in more structured administrative management. The implication of this study is the importance of digital transformation in Islamic boarding school educational institutions to improve managerial and operational quality. This study also provides insight for other educational institutions that want to develop similar digital systems to improve administrative management and communication with related stakeholders.